Understanding the Paths to Appearance- and Performance-Enhancing Drug Use in Bodybuilding - Coquet, Ronan; Roussel, Peggy; Ohl, Fabien (Frontiers in Psychology, 2018)
How do gym-goers who are normally not inclined to resort to appearance- and performance-enhancing drugs (APEDs) progressively normalize their use? Based on data collected through a year and a half of participant observation in a gym and thirty semi-directive interviews with practitioners with varying profiles in French-speaking Switzerland, this article examines the evolution of practitioners’ relations with APED use by articulating various levels of analysis. Associated with social vulnerabilities, the progressive normalization of APED use is concomitant with the “conversion” to bodybuilding. Our results show the extent to which and under what conditions interactions within the layout of gyms can influence practices. From refusal to normalization, our results suggest that APEDs and the associated beliefs coincide with career stages, which we aim to bring to light here.